GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 625114967 species occurrences available in GBIF matching the query: All data. The dataset includes 625114967 records from 13898 constituent datasets: Please see http://www.gbif.org/occurrence/download/0017476-160910150852091 for full list of all constituents.
Keywords: GBIF; biodiversity; species occurrences